Managed fragmentation of religious authority: Intra-organizational fatwa contestation within Nahdlatul Ulama in the digital age - Fathor Rahman; Pujiono; Sofkhatin Khumaidah; Muhammad Noor Harisudin (UIN Kiai Haji Achmad Siddiq Jember, 2026)
This article examines how digital platforms mediate fatwa contestation within Nahdlatul Ulama (NU) and reshape the relations among organizational, epistemic, charismatic, and digital capital. It compares two disputes: a vertical disagreement between PBNU and PCNU Jember over Friday (Jumu’ah) prayers on public roads, and a horizontal disagreement between PWNU East Java and PWNU Yogyakarta over cryptocurrency. Using qualitative digital ethnography, document analysis, and manual sentiment coding, the study traces the circulation of fatwa texts, media reports, and Facebook discussions across institutional and digital settings. The dataset comprises eight public online sources—two news reports and six Facebook posts—which generated 5,716 visible interactions: 3,594 reactions, 871 comments, and 1,251 shares. Sentiment was coded in 453 relevant comments from three cryptocurrency threads, while the remaining threads were examined qualitatively. The findings show that digital platforms make internal disagreements publicly visible while allowing them to remain institutionally manageable. Cryptocurrency discussions fostered relatively neutral and constructive inquiry, whereas the street Jumu’ah dispute produced sharper contestation over textual authority, organizational loyalty, adab, identity, and affective legitimacy. The article conceptualizes this condition as managed fragmentation within algorithmic digital authority and argues that increased digital visibility does not necessarily confer religious legitimacy.